Associations of socioeconomic status and healthy lifestyle with incident dementia and cognitive decline: two prospective cohort studiesResearch in context - Kan Wang; Yuan Fang; Ruizhi Zheng; Xuan Zhao; Siyu Wang; Jieli Lu; Weiqing Wang; Guang Ning; Yu Xu; Yufang Bi (EClinicalMedicine, 2024)
Summary: Background: Little is known about the complex associations of socioeconomic status (SES) and healthy lifestyle with cognitive dysfunction. Methods: Using data from the Health and Retirement Study (HRS) [2008–2020] and the English Longitudinal Study of Ageing (ELSA) [2004–2018], SES was constructed by latent class analysis using education level, total household income and wealth. Overall healthy lifestyle was derived using information on never smoking, low to moderate alcohol consumption (drinks/day: (0, 1] for women and (0, 2] for men), top tertile of physical activity, and active social contact. Findings: A total of 12,437 and 6565 participants from the HRS and ELSA were included (40.8% and 46.0% men and mean age 69.3 years and 65.1 years, respectively). Compared with participants of high SES, those of low SES had higher risk of incident dementia (hazard ratio 3.17, 95% confidence interval 2.72–3.69 in the HRS; 1.43, 1.09–1.86 in the ELSA), and the proportions mediated by overall lifestyle were 10.4% (7.3%–14.6%) and 2.7% (0.5%–14.0%), respectively. Compared with participants of high SES and favorable lifestyle, those with low SES and unfavorable lifestyle had a higher risk of incident dementia (4.27, 3.40–5.38 in the HRS; 2.02, 1.25–3.27 in the ELSA) and accelerated rate of global cognitive decline (β = −0.058 SD/year; 95% CI: −0.073, −0.043 in the HRS; β = −0.049 SD/year; 95% CI: −0.063, −0.035 in the ELSA). Interpretation: Unhealthy lifestyle only mediated a small proportion of the socioeconomic inequality in dementia risk in both US and UK older adults. Funding: This work was supported by grants from the National Natural Science Foundation of China (82088102 and 82370819), the National Key R&D Program of China (2023YFC2506700), the Shanghai Municipal Government (22Y31900300), the Shanghai Clinical Research Center for Metabolic Diseases (19MC1910100), the Innovative Research Team of High-Level Local Universities in Shanghai, the Special Project for Clinical Research in Health Industry of Shanghai Municipal Health Commission (202340084), and Ruijin Hospital Youth Incubation Project (KY20240805). Y.X. is supported by the National Top Young Talents program.